PENGARUH PERCAYA DIRI DAN PENGENDALIAN EMOSI DIRI TERHADAP EFIKASI GURU DIMODERASI IDEALISASI PENGARUH DI SMP NEGERI KECAMATAN JUWANA, KABUPATEN PATI - Iswahyudi, Iswahyudi; Fauzan, Moh (Jurnal Ilmiah Telaah Manajemen, 2017)
This research’s purpose is to find how the influence of self confident and emotional self control to the teacher’s efficacy moderated by Idealized influenced. The study population is a government school teachers in four Junior High School in the district Juwana, Pati regency. Sampling using proportional sampling method . The number of samples by using the formula Slovin.. Collecting the data using questionnaires . The amount of data that can be analyzed as many as 120. The data were analyzed using regression -based model of quasi moderator interaction. The results showed that ( 1 ) the dimensions of confidence affect the efficacy of teachers , ( 2 ) the dimensions of emotional self- control affect the efficacy of teachers , ( 3 ) Idealized influenced influence on the efficacy of teachers , ( 4 ) Idealized influenced moderates influence of confidence on the efficacy of teachers , ( 5 ) Idealized influenced moderates influence of emotional self- control on the efficacy of teachers . Keywords: Self confidence, emotional self control , Idealized influenced, teacher’s efficacy